Metaverse-Based Learning in the Digital Era - Jusuf, Heni; Lucia Sri Istiyowati; Muh Fauzi; Maria Magdalena; R. Eko Indrajit (JTP - Jurnal Teknologi Pendidikan, 2023)
Digital disruption in the world of education refers to the impact of technology on traditional education systems and models, where the current education system is felt to need to be adjusted to the progress of the times and the needs of students. The business model of education in this digital era requires the innovation and creativity of teachers. After the Covid 19 pandemic, in addition to providing challenges in the world of education, it also provides an opportunity where students and educators are accustomed to online learning applications, teleconference applications, or collaboration applications that were previously not or rarely used by the world of Education. Many apps have been created to make online learning easier. Metaverse has been around since 2010, but due to the pandemic, the use of metaverse in learning is again being used with the development of Virtual reality, extended reality, and augmented reality technology. These three technologies can display a virtual environment just like the original environment. The method used to design metaverse-based learning is to use the ADDIE research and development model while learning development follows the stages of the Dick and Carey model. The results of field trials using survey methods and experiments on 20 junior high school students for one semester using the metaverse, resulted in a score of 4.82 with the conclusion of excellent learning material, students felt very happy, motivated to complete tasks, and always followed the learning stages designed in the form of games. Implementing the metaverse in learning can increase student engagement, creativity, technology skills, collaboration, and interaction as well as improve learning experiences that are more fun and engaging.